NMC–NMIJ bilateral comparison of millimeter-wave attenuation in WR-15 waveguide band at 50 GHz and 54 GHz. (March 2016) - Iida, H.; Wu, T.Y.
Highlights: Attenuation measurements in WR-15 waveguide band were verified between two NMIs. The attenuation measurement systems of each NMI are based on different principles. A programmable step attenuator is used as a traveling standard at 50 GHz and 54 GHz. The degree of equivalence of the NMI standards is analyzed. The results show good agreement within their expanded uncertainties. Abstract: This paper reports on a bilateral comparison of millimeter-wave attenuation in WR-15 waveguide band between the National Metrology Institute of Japan (NMIJ) and the National Metrology Centre, A∗STAR (NMC). Different types of attenuation measurement systems were independently developed at both laboratories. The systems are based on a stabilized single-channel intermediate frequency (IF) substitution method at NMIJ, and a dual-channel audio frequency substitution method at NMC. A comparison was carried out at 50 GHz and 54 GHz using a programmable step attenuator fitted with precision coaxial to waveguide adaptors as a traveling standard. Good agreement of the measurement results between both laboratories was verified in the attenuation range up to 60 dB.